A NALYSIS OF ECONOMIC SCALE AND EFFICIENCY OF THE USE OF PRODUCTION FACTORS IN VIRGINIAN TOBACCO PRODUCTION IN BULELENG DISTRICT - A.A. Bagus Putu Widanta, Made Dwipa Mahardika (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
One of the potential tobacco producing regions in Bali Province is Buleleng Regency, which is Virginia tobacco producer. This study aims to analyze the simultaneous and partial influence of land area, labor, capital and fertilizer use on virginia tobacco production in Buleleng Regency and analyze the economic scale conditions of virginia tobacco production in Buleleng Regency and analyze the conditions for efficient use of virginia tobacco production factors in the Regency Buleleng. The number of samples used were 53 virginia tobacco farmers in Buleleng regency, using the Simple Random Sampling method. The analysis technique used in this study is multiple linear regression analysis, economic scale test and efficiency test. The results showed that the variable area of ??land, labor, capital and fertilizer use simultaneously had a significant effect on virginia tobacco production in Buleleng Regency. Partially the variable land area, capital labor and fertilizer use partially have a positive and significant effect on virginia tobacco production in Buleleng Regency. Virginia tobacco farming is on an economical scale of increasing return to scale. The use of factors in the production of land area and fertilizer use has been optimal (efficiency) in the process of virginia tobacco production in Buleleng Regency. But for labor and capital inputs in conditions that are not efficient because their use needs to be reduced.